Observer variation in the histological grading of rectal carcinoma. - Thomas, G D (1983)
The variation between two observers in grading 100 biopsies and the corresponding main specimens of rectal carcinomas has been examined. Using kappa statistics, which take account of chance agreement, we found a highly significant level of agreement. As expected, higher levels were obtained for intraobserver agreement. However, disagreements between observers were in many instances "haphazard" and there were differences in bias between them. Fifty paired biopsies and main tumours were graded by five observers and the results analysed for bias and by kappa statistics for overall and conditional agreement. These methods revealed significant overall agreement but the levels for some observer pairs did not differ significantly from chance. Examination for observer bias indicated differing standards of grading, and haphazard disagreements reached high levels for some observer pairs. The intraobserver agreement between the grade of the biopsy and the corresponding main tumour varied from 56-69% but only 52% of the poorly differentiated tumours were diagnosed as such in the preoperative biopsy by the "specialist" observer. The poor predictive value was not improved by taking multiple biopsies. We conclude that the grade of a rectal carcinoma cannot be accurately assessed on a preoperative biopsy and that this has serious implications for the management of low rectal cancers. Furthermore the wide discrepancies in diagnostic standards between some pathologists mean that studies on the treatment and prognosis of rectal cancer which utilise histological grade for comparison purposes must be viewed with considerable skepticism.